Education on ethnic-racial relations in children's education: the arts of teaching - Érica Bolzan; André da Silva Mello (Universidade Federal do Norte do Tocantins, 2023)
This article has as purpose the analysis of the arts of doing the Education on Ethnic-Racial Relations (ERER) related to the faculty members under continuous training working with Child Education in the city of Vitória/ES. It is a Collaborative Research-Action, which uses as sources the documents produced during the formation process. These documents are derived from the activities performed in virtual environment and from reflexive texts written by teachers, published as books. Through collective reflections, the faculty members could develop diverse ways to approach ERER, using folk dances and African and Afro-Brazilian literature in order to achieve their goals. As a result, it was identified that teachers make use of different languages during their pedagogical mediations, acknowledge and value the children's main role in the practices implemented by ERER. In conclusion, regarding the arts of teaching ERER, the faculty members were engaged with the Children's Education curricular dynamic itself, which is not organized in a disciplinary way, and having the presence of childhood conception in the guidance documents that search for avoiding children to be in an invisible social condition, recognizing them as active subjects in their learning and developing processes.